Piloting web-based structural competency modules among internal medicine residents and graduate students in public health - Nguemeni Tiako, Max Jordan; Rahman, Farah; Sabin, Janice; Black, Aba; Boatright, Dowin; Genao, Inginia (Frontiers in Public Health, 2022)
Introduction: Fewer than half of internal medicine program directors report any health disparities curriculum. We piloted a web-based healthcare disparities module among internal medicine (IM) residents to test effectiveness and feasibility, compared to a convenient sample of graduate students enrolled in a public health equity course. Methods: IM residents participated in an in-person session (module 1: introduction to racial and ethnic health disparities), but first, they completed a pre-module knowledge quiz. Two weeks later, they completed module 2: “unconscious associations” and a post-module knowledge quiz. For the control arm (YSPH students enrolled in a health disparities course), completion of module 1 and 2 was required by the course instructor. Results: Forty-nine IM residents and 22 YSPH students completed the pre-module quiz and Module 1. The mean (SD) score of IM residents on the pre-module quiz was 16.1/25, (2.8), and 16.6/25 (3.2) for YSPH students, with no statistically significant difference. Nineteen residents (38.8%) completed the post-module quiz with a mean score of 16.7/25 (2.2), Hedge’s g =0.23, compared to 18 (81.8%) YPPH students, whose mean (SD) score was 19.5/25 (2.1), Hedge’s g=1.05. YSPH students’ post-module quiz average was statistically significantly higher than their pre-module test, as well as the residents’ post-module test (P<0.001). In examining participants’ responses to specific questions, we found that 51% (n=25) of residents wrongly defined discrimination with an emphasis on attitudes and intent as opposed to actions and impact, compared to 22.7% (n=5) YSPH students before the module, vs 63.2% (n=12) and 88.9% (n=16) respectively after. Conclusion: After completing a healthcare disparities course, graduate students in public health saw greater gains in knowledge compared to IM residents. Residents’ responses showed knowledge gaps such as understanding discrimination, and highlight growth opportunity in terms of health equity education. Furthermore, embedding health equity education in required curricular activities may be a more effective approach.